Recoil - McNab, Andy (London : Corgi Books, 2007)
Recuperating in Switzerland after a job that cost the life of one of his closest friends, ex-deniable operator Nick Stone is looking for a quiet life. But when his private life starts to disintegrate, Nick is reluctantly forced back into action.
Keywords: Intelligence officers -- Fiction; Suspense fiction